Teachers Self-Efficacy and Employee Brand Based Equity: A Perspective of College Students - Li, Meiyang (Frontiers in Psychology, 2022)
Teachers working in institutions like to affiliate themselves with their organizations taking into account their efficacy towards jobs along with encouraging students in studies. The main objective of the present study is to identify the teachers' self-efficacy on collective self-efficacy, academic psychological capital, and students’ engagement which consequently affect brand-based equity. The population taken in this study is the college students across China, deriving a sample size of 316. The sample had been selected on the basis of convenience sampling technique. Smart PLS 3.3.5 software has been used in the present study to analyze data for structural equation modeling. Findings of the study had showed that teachers’ self efficacy does not have any impact on employee based brand equity, however, significantly affects the collective self efficacy, academic psychological capital and student engagement. Further, strong and moderate mediations have also been confirmed in the study for collective self efficacy, academic psychological capital, student engagement between the relationships of teachers self efficacy and brand based equity, however, collective self efficacy and academic psychological capital could not find any mediating significance. The results have identified the significant role of teacher’s self-efficacy for collective self-efficacy, academic psychological capital and student’s engagement. These empirical findings suggest policy implications for retention of students in the colleges across China.